Insights into immunogenicity and therapeutic strategies to mitigate the immune response in infantile-onset Pompe disease: a comprehensive systematic literature review - Kishnani, Priya S.; Van Den Hout, Johanna M. P.; Hahn, Andreas; Kronn, David; Chien, Yin-Hsiu; Han, Mei; Heuterman, Jennifer; Sparks, Susan; Glen, Colin; Daba, Nadia (Frontiers in Immunology, 2026)
IntroductionPompe disease, a rare autosomal recessive metabolic myopathy, is primarily treated with enzyme replacement therapy (ERT); however, ERT response depends on several factors, including ERT initiation age, dose, and cross-reactive immunological material (CRIM) status, especially in infantile-onset Pompe disease (IOPD).AimThis systematic literature review (SLR) focused on three research questions (1): how CRIM status is determined in patients with IOPD in clinical practice, and how CRIM-negative status impacts outcomes (2); how health professionals use CRIM status to inform their decisions on immune tolerance induction (ITI) regimens; and (3) which regimens are used in real-world clinical practice.MethodsThe SLR was conducted using Embase and PubMed databases covering the literature from January 1, 2003, to August 4, 2022. The search terms used were “Pompe or IOPD” and “cross-reactive immunological material or CRIM.” Data extraction was performed using pre-designed tables in Microsoft Excel. Among those identified, 54, 51, and 69 studies provided meaningful data for the respective research questions. The key theme was the importance of early diagnosis/treatment. Recently, there has been a major shift from direct CRIM testing using western blotting and mutation analysis to CRIM status prediction based on genetic variant analysis. The ITI regimen was mostly prescribed for CRIM-negative patients and some CRIM-positive cases in a prophylactic/naïve setting at ERT initiation to prevent the development of high antibodies and for IOPD patients irrespective of CRIM status in the ERT-experienced setting due to the presence of high and sustained anti-drug antibody levels. The frequently reported ITI regimen includes a short rituximab and methotrexate course in an ERT naïve setting, with/without intravenous immunoglobulin. CRIM-negative patients receiving ITI with ERT have better clinical outcomes than those not receiving the ITI regimen. Presently, the ITI regimen used in CRIM-positive patients is variable and based on physician preference, family history, or specific variants.ConclusionThe study concluded that CRIM status determination is important in patients with IOPD and impacts management approaches. ITI use has been predominantly reported in CRIM-negative patients to improve the clinical outcomes, with other important factors being early initiation of ERT and treatment above label dose of alglucosidase alpha and many are doing upto 40 mg/kg/2 weeks.